Epidermal Growth Factor Modulates Palmitic Acid-Induced Inflammatory and Lipid Signaling Pathways in SZ95 Sebocytes - Törőcsik, Dániel; Fazekas, Fruzsina; Póliska, Szilárd; Gregus, Andrea; Janka, Eszter Anna; Dull, Katalin; Szegedi, Andrea; Zouboulis, Christos C.; Kovács, Dóra (Frontiers in Immunology, 2021)
Epidermal growth factor (EGF) acts as a paracrine and autocrine mediator of cell proliferation and differentiation in various types of epithelial cells, such as sebocytes, which produce the lipid-rich sebum to moisturize the skin. However, sebum lipids via direct contact and by penetrating through the epidermis may have regulatory roles on epidermal and dermal cells as well. As EGF receptor (EGFR) is expressed throughout the proliferating and the lipid-producing layers of sebaceous glands (SGs) in healthy and acne-involved skin, we investigated the effect of EGF on SZ95 sebocytes and how it may alter the changes induced by palmitic acid (PA), a major sebum component with bioactive roles. We found that EGF is not only a potent stimulator of sebocyte proliferation, but also induces the secretion of interleukin (IL)6 and down-regulates the expression of genes involved in steroid and retinoid metabolism. Importantly, when applied in combination with PA, the PA-induced lipid accumulation was decreased and the cells secreted increased IL6 levels. Functional clustering of the differentially regulated genes in SZ95 sebocytes treated with EGF, PA or co-treated with EGF+PA further confirmed that EGF may be a potent inducer of hyperproliferative/inflammatory pathways (IL1 signaling), an effect being more pronounced in the presence of PA. However, while a group of inflammatory genes was up-regulated significantly in EGF+PA co-treated sebocytes, PA treatment in the absence of EGF, regulated genes only related to cell homeostasis. Meta-analysis of the gene expression profiles of whole acne tissue samples and EGF- and EGF+PA -treated SZ95 sebocytes showed that the EGF+PA co-activation of sebocytes may also have implications in disease. Altogether, our results reveal that PA-induced lipid accumulation and inflammation can be modulated by EGF in sebocytes, which also highlights the need for system biological approaches to better understand sebaceous (immuno)biology.